Peer play network in preschool classrooms: Features and variations by child characteristics and skills - Ji-Young Choi; Ziye Wen; Ashley Boros; Tzu-Jung Lin; Becky Huang; Chia-Hsin Yin (PLoS ONE, 2025)
Peers play a critical role in creating opportunities for learning. However, less is known about how children form peer play networks in preschool and how their level of connection in peer play varies based on individual characteristics and skills. This exploratory study used social network modeling to examine variations in peer play networks across preschool classrooms (N = 5), focusing on children’s play centrality and classroom network density. Data from all classroom children, including those with both active and passive parental consent, revealed similar peer play patterns at both mid-year (N = 81) and year-end (N = 79). Most children had one or more peers with whom they played frequently or always, but a small subset (3%) rarely or never engaged with playmates. Classroom network density fell within a moderate range, suggesting that children tended to select specific peers for play rather than interacting uniformly with all classmates. Analyses of play centrality among children with active consent (n = 26) revealed that dual language learners (DLLs), defined as children exposed to a language other than English at home, were less likely than their non-DLL peers to hold central positions in classroom play networks at the end of the preschool year. Additionally, the study identified a homophily effect related to problem behaviors, indicating that children were more likely to play with peers who displayed similar levels of problem behaviors. These findings highlight the importance of recognizing variations in peer play networks to foster inclusive and supportive peer play environments in early childhood education. This study underscores the need for further research into the factors that shape peer play networks in preschool settings, particularly the roles of language, culture, and behavior in influencing children’s interactions.